Neural network efficiency optimization control of a variable speed compressor motor drive - Abdul Halim Mohamed Yatim, 1959-, author; Wahyu Mulyo Utomo, author; IEEE International Electric Machines and Drives Conference (2007 : Turkey) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL